Antiobesity and Hypolipidemic Effects of Polyphenol-Rich Longan (Dimocarpus longans Lour.) Flower Water Extract in Hypercaloric-Dietary Rats - Yang, Deng-Jye; Chang, Yuan-Yen; Hsu, Chin-Lin; Liu, Cheng-Wei; Lin, Yi-Ling; Lin, Yu-Huei; Liu, Kai-Cheng; Chen, Yi-Chen (Journal of agricultural and food chemistry, 2010)
Plenty of polyphenols, i.e. phenolic acids and flavonoids, were found in longan flower water extract (LFWE) through spectrophotometric and HPLC analyses. Antiobesity and hypolipidemic effects of polyphenol-rich longan flower water extract (LFWE) were investigated in this study. Eight male rats per group were assigned randomly to one of the following dietary groups: (1) normal-caloric diet and pure water (NCD + NDW); (2) hypercaloric diet and pure water (HCD + NDW); (3) HCD and 1.25% (w/v) LFWE (HCD + 1.25% LFWE); (4) HCD and 2.5% (w/v) LFWE (HCD + 2.5% LFWE) for 9 weeks. Body weight, size of epididymal fat, serum triglyceride level and atherogenic index, and hepatic lipids were decreased (p < 0.05) in HCD rats by drinking 2.5% LFWE which may result from downregulated (p < 0.05) pancreatic lipase activity, and sterol regulatory element binding protein-1c (SREBP-1c) and fatty acid synthase (FAS) gene expressions, as well as upregulated (p < 0.05) LDL receptor (LDLR) and peroxisome proliferator-activated-receptor-alpha (PPAR-α) gene expressions, and also increased (p < 0.05) fecal triglyceride excretions. Therefore, polyphenol-rich LFWE indeed characterizes antiobesity and hypolipidemic effects in vivo.